Two chair test: a substitute of 6 min walk test appear cardiopulmonary reserve specific. Issue 1 (22nd September 2020) - Bhattacharyya, Parthasarathi; Saha, Dipanjan; Paul, Mintu; Ganguly, Dhiman; Mukherjee, Biswarup; Roy Chowdhury, Sushmita; RoyChoudhury, Sourav; Agarwal, Pawan; Halder, Indranil; Ghosh Roy, Debanu; Ray, Shuvanan
Abstract : Background: A simple and efficient exercise test possible in a small space is welcome to supplement 6 min walk test (6MWT) that demands a 100 feet corridor to perform. Methods: The proposed two chair test (2CT) makes a person to sit and move five times between two chairs placed face to face at 5 feet apart and note the changes in pulse-rate (PR) and arterial oxygen saturation (SpO2 ) at every 10 s for 2 min after that. Comparison of the post-exercise measurements (PR and SpO2 ) with a repeat performance in same patients was done for reproducibility and doing the same after 6MWT and 2CT in another set of patients was meant for for acceptability. The statistical analysis was made on moment to moment change, mean maximal difference and mean cumulative difference for the measurements using p value, z-score, r value and principal component analysis (PCA). Findings: A total of 40 and 60 volunteers were included for testing reproducibility and acceptability. On both the sets, the difference in most of comparisons between the measured variable (PR and SpO2 ) showed the p values remaining insignificant (>0.05), and z-score being <1 SD of the corresponding other and the correlation coefficients (r) remaining excellent (>0.9). Furthermore, the PCA shows complete overlapping. The post-exercise changes did not corelate the walking distance in 6MWT. Interpretation: The proposed 2CT demands small space and appears reproducible and comparable with 6MWT in terms of its post-exercise impact on PR and SpO2 . This novel test also appears more of cardiopulmonary reserve specific.